Kajian Kelayakan Jalan Angkut Menggunakan Metode AASHTO, Unsurfaced Road Condition Indeks dan California Bearing Ratio di PT Mandala Karya Prima, Kalimantan Utara: Feasibility Study of Transport Roads Using AASHTO Method, Unsurfaced Road Condition Index, and California Bearing Ratio at PT Mandala Karya Prima, North Kalimantan - Silaban, Cindy Grestina; Andini, Delita Ega; Harsiga, Edwin (MINERAL, 2025)
PT Mandala Karya Prima is facing challenges due to damage to the roadway that has caused a decline in travel hauler performance, resulting in unmet overburden production targets. The purpose of this research is to evaluate and recommend road geometry based on AASHTO methods, transport road quality based on URCI values, and transport road bearing capacity based on CBR testing using the DCP tool. The width of the straight road ranges from 26 to 47 meters, and 22 meters on curved roads. The road grade varies from 1.666% to 10.041%, and the cross slope is not formed. The superelevation is 0.0156 m/m with a curvature radius of 30.387 meters. The quality value of the transport road on Jl. Jati STA 200 – 1700 is 51-73 with a Good rating on the dry loading lane and on the post-rain loading lane with a value of 39-67 and a Fair rating. Meanwhile, the URCI value on the empty lane with dry conditions is 59-77 with a Good rating, and on the empty lane under post-rain conditions, it has a Good rating with values ranging from 32-69. The varying CBR values range from 18.1% to 31%, with an average of 25.6%, which is still below the required standard of 36.23%. Recommendations that can be made for improving access roads include road widening, spoil relocation, reformation of drainage, road material backfilling, use of graders and compactors, and patching at several points.